The effects of genres on the development of multifaceted linguistic complexity in Chinese learners of German: A longitudinal corpus analysis - Yushan Li; Yuan Li (PLoS ONE, 2025)
Genre-based research holds significant theoretical and practical importance in second language acquisition (SLA). While many L2 English writing studies have suggested argumentative writing was generally more challenging than narrative, whether this generalization applies to typologically different languages, such as German with its complex morphological and structural properties, requires further investigation. Specifically, genre effects on L2 writing development remain insufficiently understood for non-English languages, particularly regarding complexities beyond syntactic and lexical. This study examines how genre influences the development of morphological, lexical, syntactic, and cohesive complexity in elementary-intermediate Chinese learners of German over time. A longitudinal corpus of narrative and argumentative essays from 21 learners, who wrote both genres, was analyzed. The results show that genre effects were evident but not straightforward, with no genre consistently exhibiting greater complexity. Over time, learners predominantly exhibited nonlinear development patterns, suggesting the dynamic nature of SLA. Additionally, they exhibited decreasing lexical sophistication in both genres despite improvements in other complexity measures, indicating a “complexity trade-off” between linguistic subsystems. These findings contribute empirical evidence to the cross-linguistic comparisons in SLA research and suggest that curricula should incorporate diverse genres to develop multifaceted linguistic competence, with pedagogical approaches tailored to genre-specific complexity patterns and developmental trajectories.